Creation, study of physical and chemical properties of 2-((4-R-5-phenethyl-4H-1,2,4-triazole-3-yl)thio)ethanоic(propanоic, benzoic)acids and salts of 2-((4-R-5-phenethyl-4H-1,2,4-triazole-3-yl)thio)ethanoic acid - T. V. Ihnatova; A. H. Kaplaushenko; Yu. S. Frolova (Zaporozhye State Medical University, 2019)
A large number of native and foreign scientists are involved in the synthesis of 3-thio-1,2,4-triazole. Today, a huge number of drugs based on 3-thio-1,2,4-triazole has been created, including itraconazole, fluconazole, voriconazole, letrozole, thiotriazoles. It was revealed that the largest number of drugs based on the above-mentioned heterocyclic system is based on the salts of 1,2,4-triazole, therefore, the synthesis of acids and salts of 1,2,4-triazole is relevant. The purpose of the work is targeted search and creation of new biologically active compounds, derivatives of 5-phenethyl-4-R-4H-1,2,4-triazole-3-thioles, which exhibit low toxicity, as well as establishment of their physical-chemical properties. Materials and methods. The melting point has been determined by the capillary method on the PTP device. The elemental composition of the compounds has been determined on the elemental analyzer Elementar Vario L cube (Elementar Vario, Germany). The IR spectra of the synthesized compounds have been recorded on a Specord 200 (Specord, Germany) spectrophotometer in the range of 4000-500 cm-1. The 1H NMR spectra have been recorded on a Varian VXR-300 (Varian, USA) nuclear magnetic resonance spectrophotometer and decoded using the ADVASP 143 computer program. Chromato-mass spectral studies have been performed on Agilent 1260 Infinity HPLC (Agilent Technologies, USA) liquid chromatograph equipped with an Agilent 6120 mass spectrometer. Results. Two methods for the creation of 2-((4-R-5-phenethyl-4H-1,2,4-triazole-3-yl)thio)ethanoic(propanoic, benzoic)acids have been proposed. At the next stage, salts of 2-((4-R-5-phenethyl-4H-1,2,4-triazole-3-yl)thio)ethanoic acids were obtained by the interaction of 2-((4-R-5-phenethyl-4H-1,2,4-triazole-3-yl)thio)ethanoic acids with salts of Cu2+, K+ and Na+ in an alkaline medium or with methylamine (ethylamine, butylamine) in an alcohol medium. The structure of all synthesized compounds was confirmed by the complex use of elemental analysis, IR spectrophotometry and 1H NMR spectrometry, and their individuality was proved chromatographically. Conclusions. During the synthetic studies 12 new, not previously described compounds were received. Preparative synthesis procedures for 2-((4-R-5-phenethyl-4H-1,2,4-triazole-3-yl)thio)ethanoic(propanoic, benzoic)acids and salts of 2-((4-R-5-phenethyl-4H-1,2,4-triazole-3-yl)thio)ethanoic acids were created. The structure of the synthesized compounds was confirmed using a complex of modern research methods.